An Analysis of the Use of Generative Technologies in Developing Arabic Reading Skill Materials - Mohammad Rifqi Junaidi (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
Generative technologies, also known as generative artificial intelligence (AI), possess significant potential to revolutionize Arabic language educational content. AI can be used to create a more personalized, engaging, and effective learning experience, enabling students to achieve their goals. The approach used in this research is a qualitative approach (Library Research), in which the data collection technique employed is documentation, utilizing content analysis as the method of analysis using a desk study design to analyze the impact of using generative technologies (generative AI) in developing Arabic language education content. Data was collected from various reliable sources, such as scientific journals, research articles, textbooks, and official reports. Generative AI is a branch of artificial intelligence capable of producing new content, such as text, images, and audio. Generative AI has significant potential to improve the quality and accessibility of education. Generative AI has several advantages compared to traditional methods of producing educational content. Generative AI can produce customized content based on individual student needs. This research explores the use of generative AI to create creative and engaging Arabic language education content. This research found that generative AI can be used to produce different types of Arabic language education content, such as texts, stories, dialogues, and practice questions. The educational content produced by generative AI has proven to enhance student motivation and learning outcomes.